Clinical characteristics of healthcare workers with SARS-CoV-2 infection after vaccination with BNT162b2 vaccine - Lombardi, Andrea; Renisi, Giulia; Consonni, Dario; Oggioni, Massimo; Bono, Patrizia; Uceda Renteria, Sara; Piatti, Alessandra; Pesatori, Angela Cecilia; Castaldi, Silvana; Muscatello, Antonio; Riboldi, Luciano; Ceriotti, Ferruccio; et al. (BMC infectious diseases, 2022)
Background The pandemic of coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), had a significant impact worldwide. Vaccines against COVID-19 appear as a tool able to curb out mortality and reduce the circulation of the virus. Little is known so far about the clinical characteristics of individuals who developed SARS-CoV-2 infection after having received the vaccination, as well as the temporal relationship between vaccine administration and symptoms onset. Methods Retrospective cohort study among the 3219 healthcare workers (HCWs) of the Fondazione IRCCS Ospedale Maggiore Policlinico of Milano who received a full immunization with the BNT162b2 vaccine and who developed SARS-CoV-2 infection (documented through positive RT-PCR on nasopharyngeal swab) in March–April 2021. Results Overall, we have identified 15 HCWs with SARS-CoV-2 infection after vaccination, 7 (46.7%) of them were male and the mean age was 38.4 years (SD 14). In 4 of them, the presence of SARS-CoV-2 anti-nucleocapsid (anti-N) antibodies was assessed before vaccination and resulted positive in 1 case. In all HCWs the presence of SARS-CoV-2 anti-spike (anti-S1) antibodies was assessed, on average 42.2 days after the completion of vaccination, with a mean value of 2055 U/mL (SD 1927.3). SARS-CoV-2 infection was ascertained on average 56.2 days after vaccination. The mean cycle threshold (Ct) of SARS-CoV-2 PCR was 26.4, the lineage was characterized in 9 HCWs. None of the HCWs reported a primary or secondary immunodeficiency. Regarding symptoms, they were reported only by 7 (46.7%) HCWs and appeared on average 55 days after the second dose of vaccination. Of those who reported symptoms, one (14.3%) had fever, 7 (100%) rhinitis/conjunctivitis, 4 (57.1%) taste and smell alterations, none had respiratory symptoms, 4 headache/arthralgia (57.1%) and 1 gastrointestinal symptom (14.3%). All symptoms disappeared in a few days and no other unclassified symptoms were reported. Conclusions Infections occurring after vaccination with the BNT162b2 vaccine are mostly asymptomatic and are not associated with the serum titre of anti-S1 antibodies. We did not find a predominance of specific viral variants, with several lineages represented.